Neural events leading to and associated with detection of sounds under high processing load. Issue 3 (18th November 2011) - Sabri, Merav; Humphries, Colin; Binder, Jeffrey R.; Liebenthal, Einat
Abstract The neural events that lead to successful or failed detection of suprathreshold sounds are not well established. In this experiment, event‐related potentials (ERPs) and functional magnetic resonance imaging (fMRI) were recorded while participants performed two tasks: a primary difficult duration judgment task on a sequence of tones presented to one ear, and a secondary target detection task on an auditory oddball stream presented to the other ear. The paradigm was designed to elicit competition and variability in detection of auditory targets despite identical input. Successful detection of auditory targets was associated mainly with greater fMRI activity in superior parietal cortex and thalamus. In the ERPs, successful detection was linked with a larger fronto‐central negativity at 200–400 ms, and a later centro‐posterior positivity. Failure to detect targets was associated with greater fMRI signal in the default mode network, a significantly smaller electrical fronto‐central negativity and no late positivity. These findings demonstrate that variability in auditory detection is related to modulation of activity in multimodal parietal and frontal networks active ∼ 200 ms after target onset. Results are consistent with a limited capacity and late selection view of attention. Hum Brain Mapp, 2013. © 2011 Wiley Periodicals, Inc.